HUBUNGAN ANTARA BIMBINGAN ORANG TUA DENGAN MINAT BELAJAR REMAJA DI KAMPUNG MELAYU KEC. LUBUK BASUNG KAB. AGAM - Lidia Fitri; Vevi Sunarti (Universitas Negeri Padang, 2022)
This research is motivated by the low of parental guidance on adolescent learning interest in the Melayu Village, Lubuk Basung District, Agam Regency. aims to see a picture of adolescent learning interest, a picture of parental guidance and see the relationship between parental guidance and adolescent learning interest.This type of research is using a quantitative with a correlational approach. The population in this study were all teenagers in the Malay Village, Lubuk Basung District as many as 21 people. Sample was taken as much as 50% of the population of 11 people. The results of this study indicate that parenting still low, adolescent learning interest is still lacking; and there is a significant relationship between parental guidance and adolescent learning interest in the Melayu Village, Lubuk Basung District, Agam Regency. It is recommended for parents to be able to provide encouragement and motivation for children to further improve and be more active in learning activities, as well as be a guide for further researchers. keywords: parental guidance and interest in learning